Wound Healing and Toxicity Evaluation of Aloe vera Cream on Outpatients with Second Degree Burns: Effect of Aloe Veracream on wound burns - Abdolhossein Moghbel; Shahram Allipanah; Abdolazim Ghalambor (Iranian Journal of Pharmaceutical Sciences, 2007)
Aloe verais a tropical plant belonging to the Liliaceae family. It has beneficialeffects in variety of diseases. The aim of this study was to formulate a topical creamfrom A. verawith wound burn healing effect and to perform its clinical trial. Atotalof 30 patients (20 males and 10 females in the age range of 20-50 years) with seconddegree burn wounds on their both hands were selected for the study. The subjectsused A. veratopical formulation or silver sulfadiazine 1% cream on each hand asthe test and control, symmetrically. The rate of healing was measured and comparedon 0 to 18 days after treatment. Results indicated that average percent of healingwith A. veraon day 10 was 90.6% compared with silver sulfadiazine which was only29.8% (p<0.001). Toxicity monitoring of the burn surfaces during healing courseaccording to patient responses showed neither rashes, swelling, inflammation,redness, irritation, itching nor any other toxicity symptoms. Significant effect ofA. veraon burn wounds without any adverse dermal toxic effects is very promisingand it may be employed in management of burn wound, routinely.